Late results of the Royal Free Hospital prospective controlled trial of prednisolone therapy in hepatitis B surface antigen negative chronic active hepatitis. Issue 1 (January 1980) - Kirk, A P; Jain, S; Pocock, S; Thomas, H C; Sherlock, S
Abstract : A long-term follow-up of at least 10 years or until death of 44 patients taking part in a controlled prospective trial of prednisolone therapy in hepatitis B antigen negative chronic active hepatitis (lupoid hepatitis) has been performed at the Royal Free Hospital, London. Patients presenting between 1963 and 1967 were randomly allocated into control and treatment groups. Ten year life table survival curves showed a significantly improved survival in the treatment group where 63% of patients were alive at 10 years compared with only 27% in the control group (log rank test, P = 0.03). The median survival in the treatment group was 12.2 years compared with 3.3 years in the control group. The mean duration of treatment was 4.5 years. Age, presence of antinuclear factor, cirrhosis, or level of serum transaminases at presentation did not appear to affect survival. Male patients if untreated had a poorer prognosis than females (P = 0.02). The natural history of chronic active hepatitis appeared from clinical, biochemical, and histological findings to be from an active hepatitis or cirrhosis to inactive macronodular cirrhosis. Prednisolone therapy significantly improved survival by reducing mortality in the early active phase of the disease.